2020
DOI: 10.1016/j.biopsych.2020.01.020
|View full text |Cite
|
Sign up to set email alerts
|

A Physiological Instability Displayed in Hippocampal Neurons Derived From Lithium-Nonresponsive Bipolar Disorder Patients

Abstract: Background: We recently reported a hyperexcitability phenotype displayed in dentate gyrus (DG) granule neurons derived from bipolar disorder (BD) patients (1, 2) and also a hyperexcitability that appeared only in CA3 pyramidal hippocampal neurons that were derived from BD patients who responded to lithium treatment (LR) but not from BD patients who were lithium non-responders (NR) (3). Methods: Here we used our measurements of currents in neurons derived from 4 control individuals, 3 LR BD patients, and 3 NR B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 28 publications
4
41
0
Order By: Relevance
“…This instability was caused by a reduction in the sodium current and increased potassium current amplitude. The computational model further confirmed the role of increased potassium currents in BD hippocampal neuronal hyperexcitability [130]. Recently, Mishra et al (2021) studied lithium effects on circadian rhythms in BD patients' neurons.…”
Section: Lithium Treatment In Cellular Models Of Bdsupporting
confidence: 56%
“…This instability was caused by a reduction in the sodium current and increased potassium current amplitude. The computational model further confirmed the role of increased potassium currents in BD hippocampal neuronal hyperexcitability [130]. Recently, Mishra et al (2021) studied lithium effects on circadian rhythms in BD patients' neurons.…”
Section: Lithium Treatment In Cellular Models Of Bdsupporting
confidence: 56%
“…Mertens and colleagues (5) demonstrated hyperactivity in iPSC-derived dentate gyrus neurons derived from patients, which was reversed by lithium only in those derived from patients who were lithium responsive. In follow-up studies, the same group replicated these findings, successfully predicted the lithium responsiveness of a patient using a classifier trained on electrophysiological parameters of the responder vs. non-responder cells (41), and suggested that hippocampal CA3 hyperexcitability might be unique to lithium responders (42), and reduced by lithium exposure (43). However, the studies conducted to date have been used small samples and have emerged from a single laboratory.…”
Section: Psychiatric Illnesses In a Dish? The Questions Of Phenotype And Cell Typementioning
confidence: 83%
“…Mertens and colleagues (5) demonstrated hyperactivity in iPSC-derived dentate gyrus neurons derived from patients, which was reversed by lithium only in those derived from lithium-responsive patients. In follow-up studies, the same group replicated these findings, successfully predicted the lithium responsiveness of a patient using a classifier trained on electrophysiological parameters of responder vs. non-responder cells (38), and suggested that hippocampal CA3 hyperexcitability might be unique to lithium responders (39), and reduced by lithium exposure (40). However, these studies used small samples and emerged from a single laboratory.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 86%